Strategi Pemulihan Pandemi Covid-19 Bagi Sektor UMKM Di Indonesia - Nafis Dwi Kartiko; Ismi Fathia Rachmi (Jurnal Syntax Transformation, 2021)
The COVID-19 pandemic has shocked most sectors of the economy. One of the sectors that experienced the shock was the MSME sector. The government itself has launched a National Economic Recovery Program to reduce the impact on the economy. One of the concerns in the National Economic Recovery Program is the non-distribution of credit/capital to the MSME sector, still high unemployment rate due to the pandemic. One of the strategies that can be proposed to address this problem is to provide stimulus to the economy. The research was conducted using qualitative research methods to create interpretations to capture the deepest meaning. Researchers chose financial technology or fintech as an alternative solution to the problem of capital access for the MSME sector. Fintech was chosen because of its ability to improve financial transactions in the economy. Researchers also propose tax incentives for parties involved in fintech transactions in order to attract more investors and actors.